UJI KANDUNGAN SENYAWA MINYAK ATSIRI Apium graveolen L. SEBAGAI PESTISIDA NABATI Spodoptera frugiperda (Lepidopter: Noctuidae) - Trisnani Alif, Trisnani Alif; Mahindra Dewi Nur Aisyah; Christa Dyah Utami (Jurnal Matematika dan Sains (JMS), 2024)
The use of chemical pesticides to control Spodoptera frugiperda needs to be minimized by replacing organic pesticides using Apium graveolens essential oil as the main pesticide ingredient. This research aims to determine the main compounds of Apium graveolens essential oil and its potential as a botanical pesticide. This research experimental laboratory methods and product testing. Experimental tests were carried out using GCMS and product lab tests with 3 treatments concentration of essential oil and 5 replications, P0 (Control), P1 (1%), P2 (2%) and P3 (3%). The test results show that the main chemical compounds contained in Apium graveolens are ?-Caryophyllene, 1(3H)-Isobenzofuranone, 3-ethoxy, Phthalide, Cyclopentanone and 1,2-Benzenedicarboxylic acid, bis(2-ethylhexyl) ester (CAS) Bis( 2-ethylhexyl) phthalate. And there is a very significant effect of Apium Graveolens essential oil on the mortality of third instar larvae of Spodoptera frugiperda with the highest average at P4 (3%) at 92%.